Metal organic frameworks based on bioactive components. Issue 14 (27th February 2017) - Rojas, S.; Devic, T.; Horcajada, P.
Abstract : This review highlights the latest advances of Metal Organic Frameworks (MOFs) in the promising biomedical domain, from their synthesis to their biorelated activities. Abstract : One of the more recent and promising domains of the application of Metal Organic Frameworks (MOFs) is the biomedical one. To fulfil the keystone requirements of bioapplications, i.e. biosafety and activity, endogenous and/or bioactive motifs (cations, organic ligands or both) have been successfully used as constitutive building blocks to construct Metal Biomolecule Frameworks (also known as bioMOFs). This review highlights the latest advances in 3D bioMOF structures, from their synthesis to their biorelated activities in different biorelated areas including drug delivery, imaging, and sensing, classifying them by the nature of the active component.